Achilles' Choice : Examples of Modern Tragedy - Lenson, David, 1945- (Book collections on Project MUSE., 1975)
Why, during the last two hundred years, when critical achievement in the field of tragedy has been outstanding, has there been little creative practice? David Lenson examines the work of various writers not ordinarily placed in the tragic tradition-among them, Kleist, Goethe, Melville, Yeats, and Faulkner-and suggests that the tradition of tragedy does continue in genres other than drama, that is, in the novel and even in lyric poetry.The notion of tragedy's migration from one genre to others indicates, however, rather sweeping modifications in the theory of tragedy. Achilles' Choice proposes a structural model for tragic criticism that synthesizes the almost scientific theories predominant since World War II with the irrationalist theories they replaced.Originally published in 1975.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.